Діагностика остеоартрозу: вибір основних критеріїв - Андрійчук, Ольга Ярославівна; Andriіchuk, Olga Ya. (Національний педагогічний університет імені М. П. Драгоманова, 2011)
У статті розглядаються основні етапи обстеження хворих на остеоартроз, аналізуються методи та опитувальники, які найчастіше застосовуються у медичній практиці. In the article the basic stages are examined inspections patient with osteoartroz, analysed methods and questionnaires which are more frequent all used in medical practice, descriptions of the roentgenologic stages of disease and recommendation of Association of revmatologiv of Ukraine are given in relation to diagnostics.
Diagnostics of osteoartrozu: choice of basic criteria.
Keywords: остеоартроз; діагностичні критерії; опитувальники; анкети; osteoartroz; diagnostic criteria; questionnaires; questionnaires